Modified porous chitosan beads for selectively adsorbing nickel ions in a solution containing nickel and cobalt ions, preparation method thereof, and application thereof in cobalt and nickel separation

Through the preparation of modified porous chitosan beads, the synergistic effect of porous, crosslinked structure and amine methylpyridine functional groups is used to achieve selective adsorption of nickel ions, solving the environmental protection problems of traditional resins in cobalt-nickel ion adsorption separation, and achieving efficient and environmentally friendly cobalt-nickel separation effect.

CN119549126BActive Publication Date: 2025-04-11LANZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510119243.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-11
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In the prior art, traditional ion exchange resins are used for adsorption and separation of cobalt and nickel ions, which have environmental problems and are difficult to degrade naturally, and may cause potential harm to human bodies, soil and water.

Method used

A modified porous chitosan coagulation bead was developed to form a porous and cross-linked structure through polyethylene glycol pore formation and glutaraldehyde cross-linking, and grafted with epoxychlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride to obtain modified porous chitosan coagulation beads containing amine methylpyridine functional groups to achieve selective adsorption of nickel ions.

Benefits of technology

The modified porous chitosan beads show excellent nickel ion selective adsorption properties, almost does not adsorb cobalt ions, has good acid resistance and reusability, and is simple in preparation, with a wide range of raw materials and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549126B_ABST
    Figure CN119549126B_ABST
Patent Text Reader

Abstract

The present application provides a modified porous chitosan bead that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, a preparation method thereof, and an application in cobalt and nickel separation, which belongs to the technical field of chitosan preparation. The present application first uses polyethylene glycol and glutaraldehyde to modify chitosan to obtain chitosan beads with a porous, cross-linked structure, and then obtains modified porous chitosan beads containing aminomethylpyridine functional groups through grafting with epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride. The modified porous chitosan beads have excellent selective adsorption for nickel ions in a cobalt-nickel solution with a pH range of 2-5, and can achieve nickel-cobalt separation. In addition, the modified porous chitosan beads also have a good nickel-cobalt separation effect in a salt-containing system. The preparation method of the modified porous chitosan beads provided in the present application is simple in process, and the raw material chitosan is widely available, non-toxic and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chitosan preparation, and in particular to a modified porous chitosan bead for selectively adsorbing nickel ions in a solution containing nickel and cobalt ions, a preparation method thereof, and an application of the chitosan bead in cobalt and nickel separation. Background Art

[0002] Cobalt and nickel are extremely common metal elements in lithium-ion batteries and are widely present in lithium nickel manganese cobalt oxide or lithium nickel cobalt aluminum oxide cathodes. With the rapid development of the battery field, the market demand for cobalt and nickel is increasing, and the research on the recycling technology of nickel and cobalt is particularly urgent and of great significance. After a series of processes such as acid treatment and solid-liquid separation, the leaching solution produced by waste batteries is rich in cobalt ions and nickel ions. The effective separation of cobalt ions and nickel ions in the leachate plays an important role in the entire recycling process. The high separation rate can ensure that the recovered metal raw materials meet higher purity standards, so that they can be widely used in many application scenarios with extremely high requirements for material purity, especially in the fields of high-performance materials such as high-purity metals, aerospace and electronic equipment.

[0003] In actual operation, resins are commonly used to adsorb and separate nickel ions and cobalt ions. However, traditional ion exchange resins use polystyrene as the main adsorption material, which is not only environmentally friendly in the production process, but also difficult to degrade naturally after use, causing potential harm to the human body, soil and water. Therefore, how to improve the adsorption and separation materials of cobalt and nickel ions and prepare environmentally friendly adsorbents to achieve green recovery of nickel and cobalt ions at a high separation rate has become a technical problem that needs to be solved urgently.

[0004] In view of this, it is necessary to develop a modified porous chitosan bead that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, and a preparation method thereof, and an application thereof in cobalt and nickel separation, in order to solve the above problems. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a modified porous chitosan beads that selectively adsorb nickel ions in a solution containing nickel and cobalt ions, a preparation method thereof, and an application in cobalt and nickel separation. First, porous chitosan beads are prepared using polyethylene glycol as a pore-forming agent, and then the chemical stability and strength of the chitosan beads are improved by cross-linking with glutaraldehyde, while obtaining a larger molecular weight, and then modified porous chitosan beads containing aminomethylpyridine functional groups are obtained by grafting with epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride. The porous, cross-linked structure and aminomethylpyridine synergistically enable the modified porous chitosan beads prepared in the present application to exhibit excellent selective adsorption of nickel ions, and almost no adsorption of cobalt ions. The modified porous chitosan beads can be reused after acid soaking and washing after adsorption, and have excellent cobalt and nickel separation performance and chemical stability. At the same time, the preparation process of the modified porous chitosan beads provided in the present application is simple, and the raw material chitosan is widely available and environmentally friendly.

[0006] In the first aspect, the embodiment of the present application provides a modified porous chitosan bead that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, wherein the modified porous chitosan bead has a porous, cross-linked structure formed by modifying chitosan with polyethylene glycol 2000 and glutaraldehyde, and an aminomethylpyridine functional group obtained by grafting epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride, and its general structural formula is as follows:

[0007]

[0008] Wherein, n>2; the mass ratio of the chitosan to the polyethylene glycol 2000 is 1:(0.5-2); and the volume ratio of the epichlorohydrin to the ethylenediamine is (0.3-0.5):1.

[0009] Furthermore, the porous, cross-linked structure and the aminomethylpyridine functional group enable the modified porous chitosan beads to selectively adsorb nickel ions in a solution having a pH of 2-5 and containing both nickel ions and cobalt ions.

[0010] In the second aspect, an embodiment of the present application provides an application of modified porous chitosan beads that selectively adsorb nickel ions in a solution containing nickel and cobalt ions as described in any of the aforementioned schemes in cobalt and nickel separation. Under shaking conditions, the modified porous chitosan beads are put into a solution to be treated containing both nickel ions and cobalt ions for adsorption. The characteristic that the modified porous chitosan beads adsorb nickel ions much more than cobalt ions is utilized to reduce the nickel ion concentration in the solution, thereby separating the nickel ions and cobalt ions. The modified porous chitosan beads after adsorbing nickel ions are immersed and washed in a hydrochloric acid-water solution, and then washed with distilled water to desorb the adsorbed nickel ions. The desorbed modified porous chitosan beads are reused for cobalt and nickel separation.

[0011] Furthermore, the pH value of the solution to be treated is in the range of 2-5; the solution to be treated contains nickel ions and cobalt ions, or the solution to be treated contains nickel ions and cobalt ions and also contains FeSO4, MgCl2, KCl, CaCl2, ZnSO4, Al2(SO4)3 or NaCl.

[0012] Furthermore, the adsorption time of the modified porous chitosan beads in the solution to be treated is 18-30 h; the soaking and washing time of the modified porous chitosan beads in the hydrochloric acid-water solution after adsorbing nickel ions is 12-16 h; the hydrochloric acid concentration in the hydrochloric acid-water solution is 5-15 wt%; the amount of the modified porous chitosan beads as an adsorbent is 0.5-1 g / L, specifically, the amount refers to the amount calculated using the dry weight of the modified porous chitosan beads.

[0013] In a third aspect, the present invention provides a method for preparing a modified porous chitosan bead that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, comprising the following steps:

[0014] S1, chitosan and polyethylene glycol 2000 are added to an acetic acid-water solution and stirred to dissolve, and then a sodium hydroxide-water solution is added dropwise to generate a precipitate, which is filtered and washed with hot water to obtain porous chitosan beads, which are recorded as CS;

[0015] S2, adding the CS obtained in step S1 to deionized water, first adding formaldehyde-water solution to react under stirring conditions, then adding glutaraldehyde to carry out cross-linking reaction, filtering, washing, and obtaining porous, cross-linked chitosan beads, which are recorded as CS-GD;

[0016] S3, adding the CS-GD obtained in step S2 to an ethanol-water solution, first adding epichlorohydrin to react under stirring conditions, the obtained product is recorded as CS-ECH, then adding ethylenediamine to react, filtering, washing, and the obtained product is recorded as CS-EDA;

[0017] S4, soaking the CS-EDA obtained in step S3 with hydrochloric acid, then washing with deionized water until neutral, and adding it together with 2-chloromethylpyridine hydrochloride and sodium carbonate to an ethanol-water solution, heating it to 85-95°C under stirring conditions, allowing the reactants to react in a reflux system for 24-28 hours, filtering, washing, and obtaining the modified porous chitosan beads, recorded as CS-Py.

[0018] Furthermore, in step S4, the mass ratio of the CS-EDA to the 2-chloromethylpyridine hydrochloride and the sodium carbonate is (1-2): (1.5-3): 1, and the solid-liquid ratio of the CS-EDA to the ethanol-water solution is (0.01-0.02): 1 g / mL; in the ethanol-water solution, the volume ratio of ethanol to water is 1: (0.5-1); the concentration of the hydrochloric acid is 0.5-1 M, and the time for soaking the CS-EDA in the hydrochloric acid is 10-14 h; and the washing refers to washing with ethanol and deionized water in sequence.

[0019] Furthermore, in step S3, the solid-liquid ratio of the CS-GD to the ethanol-water solution is (0.01-0.02):1 g / mL; the volume ratio of the epichlorohydrin, the ethylenediamine and the ethanol-water solution is (0.3-0.5):1:40; in the ethanol-water solution, the volume ratio of ethanol to water is 1:(0.5-1); the reaction temperature is 40-60 ° C, and the time is 6-12h; the washing refers to washing with ethanol and deionized water in turn.

[0020] Furthermore, in step S1, the mass ratio of the chitosan to the polyethylene glycol 2000 is 1:(0.5-2), the solid-liquid ratio of the chitosan to the acetic acid-water solution is (0.02-0.05):1 g / mL, the volume ratio of the sodium hydroxide-water solution to the acetic acid-water solution is (5-10):1; the acetic acid concentration in the acetic acid-water solution is (0.5-1)%, and the sodium hydroxide concentration in the sodium hydroxide-water solution is (0.5-1)%.

[0021] Furthermore, in step S2, the solid-liquid ratio of the CS to deionized water is (0.01-0.02):1 g / mL, and the volume ratio of the glutaraldehyde to deionized water is (0.005-0.015):1; the concentration of the formaldehyde-water solution is 37-40%, the reaction temperature of the CS and the formaldehyde-water solution is 35-45°C, and the reaction time is 2-4 h; after the CS reacts with the formaldehyde-water solution, the temperature for the cross-linking reaction with the glutaraldehyde is 40-60°C, and the reaction time is 2-6 h; the washing refers to washing with deethanol and deionized water in turn.

[0022] The beneficial effects of this application are as follows:

[0023] The present application provides a modified porous chitosan bead that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, and a preparation method thereof, as well as an application in cobalt and nickel separation. First, porous chitosan beads are prepared using polyethylene glycol as a pore-forming agent, and then the chemical stability and strength of the chitosan beads are improved by cross-linking with glutaraldehyde, while obtaining a larger molecular weight. Then, modified porous chitosan beads containing aminomethylpyridine functional groups are obtained by grafting with epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride. The porous and cross-linked structure works synergistically with aminomethylpyridine, so that the modified porous chitosan beads prepared in the present application exhibit excellent selective adsorption of nickel ions, almost no adsorption of cobalt ions, and good acid resistance.

[0024] (1) The modified porous chitosan beads prepared in the present application exhibit ultra-high selectivity for nickel ions, and selectively adsorb nickel ions in a solution containing both nickel ions and cobalt ions. The modified porous chitosan beads can be reused after acid soaking and washing after adsorption, and have excellent cobalt-nickel separation performance and chemical stability, especially acid resistance.

[0025] (2) The modified porous chitosan beads prepared in this application can separate nickel ions and cobalt ions in a wide pH range (pH = 2-5). In addition, the modified porous chitosan beads prepared in this application are also suitable for use in salt systems containing FeSO4, MgCl2, KCl, CaCl2, ZnSO4, Al2(SO4)3 or NaCl, and still have excellent cobalt-nickel separation performance at a salt concentration greater than 500 mg / L.

[0026] (3) The preparation process of the modified porous chitosan beads provided in this application is simple, and the raw material chitosan is widely available and environmentally friendly, providing a new idea for the preparation of environmentally friendly adsorption materials for cobalt and nickel separation.

[0027] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 A flow chart for the preparation of modified porous chitosan beads provided in this application;

[0030] Figure 2 Fourier transform infrared spectra of chitosan raw material CS1 used in Example 1 of the present application and CS-GD1, CS-EDA1 and CS-Py1 prepared in Example 1;

[0031] Figure 3 The scanning electron microscope (SEM) images of CS-Py1 prepared in Example 1 of the present application, wherein (a) is a SEM image obtained by magnifying 30 times, and (b) is a SEM image obtained by magnifying 5k times;

[0032] Figure 4 This is a graph showing the acid resistance of CS-Py1 prepared in Example 1 of the present application in aqueous sulfuric acid solutions with pH values ​​of 1, 2, 3, 4, and 5, respectively;

[0033] Figure 5 A comparison chart showing the variation of the adsorption amount of CS-Py1 prepared in Example 1 of the present application when it adsorbs nickel ions alone and when it adsorbs cobalt ions alone with the ion concentration;

[0034] Figure 6 This is a graph showing the adsorption of nickel ions and cobalt ions by CS-Py1 prepared in Example 1 of the present application in a nickel-cobalt mixed ion solution with a pH of 1-5;

[0035] Figure 7 This is a graph showing the adsorption of nickel ions and cobalt ions by CS-EDA4 prepared in Comparative Example 1 of the present application in a nickel-cobalt mixed ion solution with a pH of 1-5;

[0036] Figure 8 This is a graph showing the adsorption of nickel ions and cobalt ions by CS-GD-free Py prepared in Comparative Example 2 of the present application in a nickel-cobalt mixed ion solution with a pH of 1-5;

[0037] Fig. 9 This is a graph showing the adsorption of nickel and cobalt by CS-Py1 prepared in Example 1 of the present application in a salt-containing system. DETAILED DESCRIPTION

[0038] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0040] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0041] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0042] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0043] The structure, performance and preparation method of the adsorbent greatly affect the cobalt-nickel separation effect in the ion exchange adsorption method and the cost of the recovery process. In the prior art, resins are commonly used to adsorb and separate nickel ions and cobalt ions. However, traditional ion exchange resins use polystyrene as the main adsorption material, which is not only environmentally friendly in the production process, but also difficult to degrade naturally after use. Long-term existence in the environment poses potential hazards to the human body, soil and water. Therefore, how to improve the adsorption materials of cobalt and nickel ions and prepare environmentally friendly adsorbents to achieve green recovery of nickel and cobalt ions at a high separation rate has become a technical problem that needs to be solved urgently.

[0044] In order to solve the above-mentioned technical problems, the present application provides a modified porous chitosan bead that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, a preparation method thereof, and an application in cobalt and nickel separation, wherein chitosan is first modified using polyethylene glycol and glutaraldehyde to obtain chitosan beads with stable chemical properties, high strength, and a porous, cross-linked structure, and then modified chitosan beads containing aminomethylpyridine functional groups are obtained by grafting with epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride. The modified porous chitosan beads prepared in the present application show significant differences in the adsorption amount of nickel ions and cobalt ions, and the preparation method is simple, reusable, and has a wide range of applications. They can be used in acidic environments and salt-containing systems with a pH value between 2-5.

[0045] First, see Figure 1The present invention provides a method for preparing modified porous chitosan beads that selectively adsorb nickel ions in a solution containing nickel and cobalt ions, comprising the following steps:

[0046] S1, chitosan and polyethylene glycol 2000 (PEG 2000) are added to an acetic acid-water solution and stirred to dissolve, and then a sodium hydroxide-water solution is added dropwise to generate a precipitate, the solution is filtered to remove, and the solution is washed with hot water to obtain porous chitosan beads, which are recorded as CS.

[0047] In some embodiments, the mass ratio of chitosan to PEG 2000 is 1:(0.5-2), the solid-liquid ratio of chitosan to acetic acid-aqueous solution is (0.02-0.05):1 g / mL, the volume ratio of sodium hydroxide-aqueous solution to acetic acid-aqueous solution is (5-10):1; the concentration of acetic acid in the acetic acid-aqueous solution is (0.5-1)%, and the concentration of sodium hydroxide in the sodium hydroxide-aqueous solution is (0.5-1)%.

[0048] S2, adding the CS obtained in step S1 to deionized water, first adding formaldehyde-water solution under stirring at 35-45 °C for 2-4 h to protect part of the amino groups, then adding glutaraldehyde, reacting at 40-60 °C for 2-6 h, filtering, washing with ethanol and deionized water successively, to obtain porous, cross-linked chitosan beads, recorded as CS-GD.

[0049] In some embodiments, the solid-liquid ratio of CS to deionized water is (0.01-0.02):1 g / mL, the concentration of the formaldehyde-water solution is 37-40%, and the volume ratio of glutaraldehyde to deionized water is (0.005-0.015):1.

[0050] S3, adding the CS-GD obtained in step S2 to an ethanol-water solution, first adding epichlorohydrin under stirring conditions, reacting at 40-60°C for 6-12 h, the obtained product is recorded as CS-ECH, then continuing to add ethylenediamine, reacting at 40-60°C for 6-12 h, filtering to remove the solution, washing with ethanol and deionized water in turn, and the obtained product is recorded as CS-EDA.

[0051] In some embodiments, the solid-liquid ratio of CS-GD to ethanol-water solution is (0.01-0.02):1 g / mL, the volume ratio of epichlorohydrin, ethylenediamine and ethanol-water solution is (0.3-0.5):1:40, and in the ethanol-water solution, the volume ratio of ethanol to water is 1:(0.5-1).

[0052] S4, soak the CS-EDA obtained in step S3 in 0.5-1 M hydrochloric acid for 10-14 h to release the protected amino group in step S2, then wash it with deionized water until neutral, add it to an ethanol-water solution together with 2-chloromethylpyridine hydrochloride and sodium carbonate, heat it to 85-95 ° C under stirring conditions, react the reactants in the reflux system for 24-28 h, filter, wash it with ethanol and deionized water successively, and obtain modified porous chitosan beads, recorded as CS-Py.

[0053] In some embodiments, the mass ratio of CS-EDA to 2-chloromethylpyridine hydrochloride and sodium carbonate is (1-2):(1.5-3):1, the solid-liquid ratio of CS-EDA to ethanol-water solution is (0.01-0.02):1 g / mL, and the volume ratio of ethanol to water in the ethanol-water solution is 1:(0.5-1).

[0054] In a second aspect, the present invention provides a modified porous chitosan bead (CS-Py) that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, and the general structural formula thereof is as follows:

[0055]

[0056] Among them, n>2.

[0057] In some embodiments, the modified porous chitosan beads have a porous, cross-linked structure formed by modification with polyethylene glycol and glutaraldehyde, which makes the chitosan have higher strength and better chemical stability, and aminomethylpyridine functional groups obtained by grafting epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride. The porous, cross-linked structure and aminomethylpyridine work synergistically, so that the modified porous chitosan beads can selectively adsorb nickel ions in a solution containing nickel ions and cobalt ions at pH = 2-5.

[0058] The aminomethylpyridine obtained by grafting epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride makes the modified porous chitosan beads have super high selectivity for nickel ions, but the adsorption performance for cobalt ions is very poor. This is because, firstly, the cross-linking effect of glutaraldehyde improves the acid resistance of chitosan, making it have higher strength and stability, as well as a larger molecular weight; secondly, the grafted aminomethylpyridine contains three chelated nitrogen donor atoms, and the pKa value of the chelated nitrogen donor atom is low. Even under strong acidic conditions, the N atom on the pyridine can be deprotonated to adsorb the ions; thirdly, the ability of nickel ions to deprotonate is higher than that of cobalt ions, making CS-Py more selective for nickel ions than for cobalt ions.

[0059] In some embodiments, the modified porous chitosan beads exhibit excellent acid resistance, and their structure and performance remain stable in a strong acidic environment of pH = 2, and cobalt and nickel can still be separated by selective adsorption of nickel ions.

[0060] On the third aspect, the embodiment of the present application provides an application of modified porous chitosan beads that selectively adsorb nickel ions in a solution containing nickel and cobalt ions in the separation of cobalt and nickel. Specifically, under oscillation conditions, the modified porous chitosan beads are placed in a solution to be treated that contains both nickel ions and cobalt ions for adsorption for 18-30 hours. The modified porous chitosan beads are used to reduce the concentration of nickel ions in the solution by taking advantage of the fact that the adsorption rate of nickel ions is much higher than that of cobalt ions, thereby separating nickel ions from cobalt ions. The modified porous chitosan beads that have adsorbed nickel ions are immersed and washed in a hydrochloric acid-water solution with a concentration of 5-15 wt% for 12-16 hours, and then washed with distilled water to desorb the adsorbed nickel ions. The modified porous chitosan beads after desorption are reused for cobalt and nickel separation, and the adsorption performance for nickel ions is not significantly reduced. In this application, only modified porous chitosan beads are used as adsorbents, and the amount of adsorbent used is 0.5-1 g / L, which refers to the amount calculated using the dry weight of the modified porous chitosan beads.

[0061] In some embodiments, the solution to be treated may also be a salt-containing system, which means that the solution to be treated contains, in addition to nickel ions and cobalt ions, one or more salts of FeSO4, MgCl2, KCl, CaCl2, ZnSO4, Al2(SO4)3, and NaCl.

[0062] The present application uses modified porous chitosan beads to separate nickel and cobalt ions in a simple manner, without the need to add other reagents as an aid, and can process nickel and cobalt ion solutions with a pH value between 2 and 5, and has a wide range of applications. When the nickel and cobalt ion solution contains a high concentration of salt (greater than or equal to 500 mg / L), the modified porous chitosan beads can still selectively adsorb nickel ions to achieve the separation of cobalt and nickel.

[0063] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0064] Example 1

[0065] Example 1 provides a method for preparing modified porous chitosan beads. Figure 1 As shown, the following steps are included:

[0066] S1, 2 g chitosan and 4 g PEG 2000 were added to 100 mL 1% acetic acid-water solution and stirred to dissolve, 500 mL 1% sodium hydroxide-water solution was dropped into it to generate a precipitate, which was then filtered and washed with hot water to obtain porous chitosan beads, which were recorded as CS1.

[0067] S2, add CS1 obtained in step S1 to 200 mL of deionized water, and under stirring, first add 2.5 mL of 37-40% formaldehyde-water solution and react at 40 °C for 2 h to protect some amino groups, then add 2.5 mL of glutaraldehyde and react at 60 °C for 4 h, filter, wash with ethanol and deionized water successively, and obtain porous, cross-linked chitosan beads, recorded as CS-GD1.

[0068] S3, add the CS-GD1 obtained in step S2 to 200 mL of ethanol-water solution (V 乙醇 :V 水 =1:1), under stirring conditions, first add 2.5 mL of epichlorohydrin and react at 60 °C for 12 h to obtain a product, recorded as CS-ECH1, then continue to add 5 mL of ethylenediamine, react at 60 °C for 12 h, filter, wash with ethanol and deionized water in turn, to obtain a product, recorded as CS-EDA1.

[0069] S4, soak the CS-EDA1 obtained in step S3 in 0.5 M hydrochloric acid for 12 h to release the protected amino group in step S2, then wash with deionized water until neutral, and add 3 g of 2-chloromethylpyridine hydrochloride and 1.5 g of sodium carbonate to 100 mL of ethanol-water solution (V 乙醇 :V 水 =1:1), heated to 85-95 °C under stirring, and the reactants were allowed to react in a reflux system for 24 h, filtered, and washed with ethanol and deionized water to obtain modified porous chitosan beads, which were recorded as CS-Py1.

[0070] The general structural formula of CS-Py1 prepared in Example 1 is as follows:

[0071]

[0072] Where n>2.

[0073] The potassium bromide tablet method was used at 4000-500 cm -1 The chitosan raw material CS1 and CS-GD1, CS-EDA1 and CS-Py1 prepared in Example 1 were tested by Fourier transform infrared spectroscopy (FT-IR) within the wave number range. The Fourier transform infrared spectra obtained by the test are shown in FIG. Figure 2As shown in Figure 2, it can be seen that compared with CS1, the spectrum of CS-Py1 is at 1600 cm −1 and 1440 cm −1 A new aromatic skeleton vibration absorption band appears near 765 cm −1 The newly appeared aromatic C−H out-of-plane bending vibration absorption band nearby indicates that the pyridine ring has been successfully grafted onto the chitosan molecular chain.

[0074] The morphology of CS-Py1 prepared in Example 1 was characterized by scanning electron microscopy (SEM). Figure 3 As shown, (a) is a SEM image obtained by magnifying 30 times, and (b) is a SEM image obtained by magnifying 5k times. It can be seen that the diameter of CS-Py1 prepared in Example 1 is about 2 mm, and the surface has a porous structure.

[0075] The same mass of CS-Py1 was immersed in sulfuric acid aqueous solutions with pH values ​​of 1, 2, 3, 4, and 5 for 24 h, then taken out and weighed, and the masses of CS-Py1 before and after immersion were compared to test the acid resistance of CS-Py1 prepared in Example 1. The test results are shown in Figure 4 It can be seen that after being immersed in sulfuric acid aqueous solution with pH values ​​of 1, 2, 3, 4, and 5 for 24 h, the mass of CS-Py1 did not suffer obvious loss, indicating that the modified porous chitosan beads prepared in this application have good stability.

[0076] Example 2

[0077] Example 2 provides a method for preparing modified porous chitosan beads. Figure 1 As shown, the following steps are included:

[0078] S1, 2 g chitosan and 2 g PEG 2000 were added to 100 mL 1% acetic acid-water solution and stirred to dissolve, 500 mL 1% sodium hydroxide-water solution was dropped to generate a precipitate, which was then filtered and washed with hot water to obtain porous chitosan beads, recorded as CS2.

[0079] S2, add CS2 obtained in step S1 to 200 mL of deionized water, and under stirring, first add 2.5 mL of 37-40% formaldehyde-water solution and react at 40 °C for 2 h to protect some amino groups, then add 2 mL of glutaraldehyde and react at 60 °C for 4 h, filter, wash with ethanol and deionized water successively, and obtain porous, cross-linked chitosan beads, recorded as CS-GD2.

[0080] S3, add the CS-GD2 obtained in step S2 to 200 mL of ethanol-water solution (V 乙醇 :V水 =1:1), under stirring conditions, first add 2 mL of epichlorohydrin and react at 60 °C for 12 h to obtain a product, recorded as CS-ECH2, then continue to add 5 mL of ethylenediamine and react at 60 °C for 12 h, filter, wash with ethanol and deionized water successively to obtain a product, recorded as CS-EDA2.

[0081] S4, soak the CS-EDA2 obtained in step S3 in 0.5 M hydrochloric acid for 12 h to release the protected amino group in step S2, then wash with deionized water until neutral, and add it together with 2 g 2-chloromethylpyridine hydrochloride and 1.5 g sodium carbonate into 100 mL ethanol-water solution (V 乙醇 :V 水 =1:1), heated to 85-95 °C under stirring, and the reactants were reacted in a reflux system for 24 h, filtered, and washed with ethanol and deionized water to obtain modified porous chitosan beads, which were recorded as CS-Py2.

[0082] The general structural formula of CS-Py2 prepared in Example 2 is the same as that in Example 1 and will not be repeated here.

[0083] Example 3

[0084] Example 3 provides a method for preparing modified porous chitosan beads. Figure 1 As shown, the following steps are included:

[0085] S1, 2 g chitosan and 1 g PEG 2000 were added to 100 mL 1% acetic acid-water solution and stirred to dissolve, and then 500 mL 1% sodium hydroxide-water solution was dropped to generate a precipitate, which was then filtered and washed with hot water to obtain chitosan beads, recorded as CS3.

[0086] S2, add CS3 obtained in step S1 to 200 mL of deionized water, and under stirring, first add 2.5 mL of 37-40% formaldehyde-water solution and react at 40 °C for 2 h to protect some amino groups, then add 1.5 mL of glutaraldehyde and react at 60 °C for 4 h, filter, wash with ethanol and deionized water successively, and obtain porous cross-linked chitosan beads, recorded as CS-GD3.

[0087] S3, add the CS-GD3 obtained in step S2 to 200 mL of ethanol-water solution (V 乙醇 :V 水=1:1), under stirring conditions, first add 1.5 mL of epichlorohydrin and react at 60 °C for 12 h to obtain a product, recorded as CS-ECH3, then continue to add 5 mL of ethylenediamine, react at 60 °C for 12 h, filter, wash with ethanol and deionized water in turn, to obtain a product, recorded as CS-EDA3.

[0088] S4, soak the CS-EDA3 obtained in step S3 in 0.5 M hydrochloric acid for 12 h to release the protected amino group in step S2, then wash with deionized water until neutral, and add 1.5 g 2-chloromethylpyridine hydrochloride and 1.5 g sodium carbonate to 100 mL ethanol-water solution (V 乙醇 :V 水 =1:1), heated to 85-95 °C under stirring, and the reactants were reacted in a reflux system for 24 h, filtered, and washed with ethanol and deionized water to obtain modified porous chitosan beads, which were recorded as CS-Py3.

[0089] The general structural formula of CS-Py3 prepared in Example 3 is the same as that in Example 1 and will not be repeated here.

[0090] Comparative Example 1

[0091] The difference between Comparative Example 1 and Example 1 is that the original step S4 is deleted, 2-chloromethylpyridine hydrochloride is not used for grafting, and the other steps are the same as Example 1, which will not be repeated here. The final product prepared in Comparative Example 1 is recorded as CS-EDA4, which has the same structure as CS-EDA1 prepared in Example 1.

[0092] Comparative Example 2

[0093] The difference between Comparative Example 2 and Example 1 is that the original step S2 is deleted, and CS is not cross-linked with glutaraldehyde, and the following steps are included:

[0094] S1, add 2 g chitosan and 4 g PEG 2000 into 100 mL 1% acetic acid-water solution and stir to dissolve, drop 500 mL 1% sodium hydroxide-water solution to generate a precipitate, then filter and wash with hot water to obtain chitosan beads, recorded as CS5.

[0095] S2, add CS5 obtained in step S1 to 200 mL ethanol-water solution (V 乙醇 :V 水 =1:1), under stirring conditions, first add 2.5 mL of epichlorohydrin and react at 60 °C for 12 h, then add 5 mL of ethylenediamine and react at 60 °C for 12 h, filter, wash with deethanol and deionized water to obtain the product, which is recorded as CS-EDA5.

[0096] S3, add CS-EDA5 obtained in step S2, 3 g 2-chloromethylpyridine hydrochloride, and 1.5 g sodium carbonate into 100 mL ethanol-water solution (V 乙醇 :V 水 =1:1), heated to 85-95 °C under stirring, the reactants were reacted in a reflux system for 24 h, filtered, washed with ethanol and deionized water, and then washed with deionized water to obtain the final product, which was recorded as CS-free GD-Py.

[0097] Application Example 1

[0098] This application example uses CS-Py1, CS-Py2, CS-Py3, CS-EDA4, and CS-GD-free prepared in Examples 1-3 and Comparative Examples 1-2 as adsorbents, respectively, to provide an application of modified porous chitosan beads in cobalt-nickel separation, including the following steps:

[0099] S1, 10 mg of CS-Py1, CS-Py2, CS-Py3, CS-EDA4, and CS-GD-free Py were taken as adsorbents and respectively put into a mixed solution of nickel and cobalt ions with pH = 2, an initial concentration of nickel ions of 50 mg / L, and an initial concentration of cobalt ions of 50 mg / L for 24 h of oscillation adsorption. Then, the adsorbent was filtered out, and the remaining nickel ion concentration and cobalt ion concentration in the filtrate were determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the adsorption amount was calculated respectively. The adsorption amount measured for the first adsorption is shown in the table below.

[0100]

[0101] Referring to the above table, it can be seen that the CS-EDA4 obtained without 2-chloromethylpyridine hydrochloride for grafting (Comparative Example 1) has very poor adsorption of nickel ions and cobalt ions in a strong acid system (pH = 2), and the two cannot be separated by adsorption; compared with CS-Py1, CS-Py2, and CS-Py3, the CS-GD-free Py obtained without glutaraldehyde cross-linking (Comparative Example 2) has a low adsorption capacity for nickel ions and a high adsorption capacity for cobalt ions, resulting in a poor effect of nickel-cobalt separation.

[0102] S2, the adsorbents CS-Py1, CS-Py2, and CS-Py3 adsorbed with nickel ions filtered out in step S1 are immersed and washed in a hydrochloric acid solution (5-15wt%) for 12 h, then washed with distilled water for 5 times, and then respectively placed in a nickel ion solution with an initial concentration of 50 mg / L and a pH value of 2 for 24 h of vibration adsorption. Then, the adsorbent is filtered out, and the remaining nickel ion concentration in the filtrate is determined by an inductively coupled plasma optical emission spectrometer (ICP-OES), and the adsorption amount is calculated. The adsorption amount measured by the second adsorption is shown in the table below.

[0103]

[0104] Referring to the above table, it can be seen that CS-Py1, CS-Py2, and CS-Py3 can be reused for adsorbing nickel ions after acid washing and desorption, and compared with the test data of the first adsorption, the adsorption amount of nickel ions is only slightly reduced, indicating that the modified porous chitosan beads prepared in this application can be recycled.

[0105] The performance of CS-Py1 prepared in Example 1 in adsorbing nickel ions and cobalt ions was tested separately. The specific steps were as follows: 10 mg of CS-Py1 was taken as an adsorbent and placed in a nickel ion solution / cobalt ion solution with a pH of 2 and an initial concentration of 10, 20, 30, 40, 50, and 100 mg / L for 24 h of oscillation adsorption. Then, the adsorbent was filtered out and the nickel ion concentration / cobalt ion concentration remaining in the filtrate was measured by inductively coupled plasma optical emission spectrometry (ICP-OES). The test results are shown in Figure 5 shown.

[0106] See also Figure 5 It can be seen that when nickel and cobalt are adsorbed alone, with the increase of ion concentration, the adsorption amount of nickel ions by CS-Py1 increases significantly, while the increase in the adsorption amount of cobalt ions is smaller.

[0107] Application Example 2-5

[0108] Application Examples 2-5 use CS-Py1, CS-EDA4 and CS-GD-Py (without glutaraldehyde) prepared in Example 1 and Comparative Examples 1 and 2 as adsorbents, respectively, to provide an application of modified porous chitosan beads in cobalt-nickel separation. The difference between Application Examples 2-5 and Application Example 1 is that the pH values ​​of the nickel-cobalt ion solution are 1, 3, 4, and 5, respectively, and only the adsorption amount of the first adsorption is tested, and the rest is the same as Application Example 1, which will not be repeated here. The measured adsorption amount is shown in the table below.

[0109]

[0110] See also Figures 6 to 8As shown in the figure, it is the adsorption amount of nickel and cobalt by CS-Py1, CS-EDA4 and CS-GD-Py in the mixed solution of nickel and cobalt ions with pH of 1-5. Combined with the above table, it can be seen that CS-Py1 selectively selects nickel ions at pH=2-5, and has good adsorption performance, and basically does not adsorb cobalt ions, so it has a good cobalt-nickel separation effect in a wide pH range. Although CS-EDA4 basically does not adsorb cobalt ions in a strongly acidic environment (pH=2-5), the nickel-cobalt separation effect is not good due to its relatively low adsorption rate for nickel ions. Although the adsorption amount of nickel ions by CS-GD-Py is slightly higher than that of CS-EDA4, its adsorption amount of cobalt ions is the highest among CS-Py1, CS-EDA4 and CS-GD-Py, indicating that CS-GD-Py will remove more cobalt ions while removing nickel ions by adsorption, which leads to poor cobalt-nickel separation effect.

[0111] Without glutaraldehyde crosslinking or 2-chloromethylpyridine hydrochloride grafting, the expected cobalt-nickel separation effect cannot be obtained. This is because, firstly, the amino group in chitosan can undergo condensation reaction with the carbonyl group in glutaraldehyde to form a chemical crosslinking structure, so that a three-dimensional network structure is formed between chitosan molecules. This porous and crosslinked structure makes the chitosan material have higher strength and chemical stability, combined with its larger molecular weight, which is conducive to increasing the adsorption of nickel by chitosan; secondly, the aminomethylpyridine obtained by grafting contains three chelated nitrogen donor atoms, which come from weakly basic pyridine and tertiary amine functional groups respectively. The electron-withdrawing effect of the aromatic group leads to a low pKa value of the two chelated nitrogen donor atoms. Even under acidic conditions, the N atom on the pyridine can be deprotonated to adsorb ions. Thirdly, the ability of nickel ions to deprotonate is higher than that of cobalt ions, so that the selectivity of CS-Py1 for nickel ions is higher than that for cobalt ions. Therefore, only when the adsorbent has a high strength and stability while having an aminomethylpyridine structure can the ideal cobalt-nickel separation effect be achieved under acidic conditions.

[0112] Application Example 6-12

[0113] Application Example 6-12 uses CS-Py1 prepared in Example 1 as an adsorbent to provide an application of modified porous chitosan beads for separating cobalt and nickel in a salt-containing system. The difference between Application Example 6-12 and Application Example 1 is that the nickel-cobalt ion solution also includes any salt of FeSO4, MgCl2, KCl, CaCl2, ZnSO4, Al2(SO4)3, and NaCl at a concentration of 500 mg / L, as shown in the table below. The rest is the same as Application Example 1 and will not be repeated here.

[0114]

[0115] See also Fig. 9The figure shows the adsorption of nickel and cobalt by CS-Py1 in a salt-containing system. It can be seen that CS-Py1 can selectively adsorb nickel ions and separate nickel and cobalt when there are high concentrations of other ions in addition to nickel and cobalt ions in the system, indicating that the modified porous chitosan beads prepared in this application can be used for the separation of cobalt and nickel in high-concentration salt solutions.

[0116] In summary, the present application provides a modified porous chitosan beads that selectively adsorb nickel ions in a solution containing nickel and cobalt ions, a preparation method thereof, and an application in cobalt and nickel separation, wherein porous, cross-linked chitosan beads are obtained by pore formation with polyethylene glycol and cross-linking with glutaraldehyde, so that they have higher strength and chemical stability, as well as a larger molecular weight, and then modified porous chitosan beads containing aminomethylpyridine functional groups are obtained by grafting with epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride. The porous, cross-linked structure and aminomethylpyridine act synergistically, so that the modified porous chitosan beads prepared in the present application show obvious adsorption selectivity for nickel ions, selectively adsorb nickel ions in a solution containing both nickel ions and cobalt ions, and the adsorption amount increases with the increase of nickel ion concentration. The modified porous chitosan beads after adsorption can be reused after soaking and washing. The modified porous chitosan beads prepared in the present application have a wide range of applications, and have good cobalt-nickel separation effects in an acidic environment of pH=2-5 and in a salt-containing system. No other additives or adsorbents need to be added during application, and the operation is simple.

[0117] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A modified porous chitosan bead that selectively adsorbs nickel ions in a solution containing nickel and cobalt ions, characterized in that: The modified porous chitosan beads have a porous, cross-linked structure formed by modifying chitosan with polyethylene glycol 2000 and glutaraldehyde, and an aminomethylpyridine functional group obtained by grafting epichlorohydrin, ethylenediamine, and 2-chloromethylpyridine hydrochloride. Its general structural formula is as follows: Wherein, n>2; the mass ratio of the chitosan to the polyethylene glycol 2000 is 1:(0.5-2); and the volume ratio of the epichlorohydrin to the ethylenediamine is (0.3-0.5):

1.

2. The modified porous chitosan beads for selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to claim 1, characterized in that: The porous, cross-linked structure and the aminomethylpyridine functional group enable the modified porous chitosan beads to selectively adsorb nickel ions in a solution having a pH of 2-5 and containing both nickel ions and cobalt ions.

3. Use of the modified porous chitosan beads for selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to any one of claims 1 to 2 in the separation of cobalt and nickel, characterized in that: Under shaking conditions, the modified porous chitosan beads are put into a solution to be treated containing both nickel ions and cobalt ions for adsorption, and the concentration of nickel ions in the solution is reduced by utilizing the characteristic that the modified porous chitosan beads have a much higher adsorption capacity for nickel ions than for cobalt ions, thereby separating nickel ions from cobalt ions; The modified porous chitosan beads after adsorbing nickel ions are soaked and washed in a hydrochloric acid-water solution, and then washed with distilled water to desorb the adsorbed nickel ions. The desorbed modified porous chitosan beads are reused for cobalt and nickel separation.

4. The use of the modified porous chitosan beads for selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to claim 3 in the separation of cobalt and nickel, characterized in that: The pH value of the solution to be treated is in the range of 2-5; the solution to be treated contains nickel ions and cobalt ions, or the solution to be treated contains nickel ions and cobalt ions and also contains FeSO4, MgCl2, KCl, CaCl2, ZnSO4, Al2(SO4)3 or NaCl.

5. The use of the modified porous chitosan beads for selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to claim 3 in the separation of cobalt and nickel, characterized in that: The adsorption time of the modified porous chitosan beads in the solution to be treated is 18-30 h; the soaking and washing time of the modified porous chitosan beads in the hydrochloric acid-water solution after adsorbing nickel ions is 12-16 h; the hydrochloric acid concentration in the hydrochloric acid-water solution is 5-15 wt%; the amount of the modified porous chitosan beads as an adsorbent is 0.5-1 g / L, specifically, the amount refers to the amount calculated using the dry weight of the modified porous chitosan beads.

6. A method for preparing modified porous chitosan beads capable of selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to any one of claims 1 to 2, characterized in that: The steps include: S1, chitosan and polyethylene glycol 2000 are added to an acetic acid-water solution and stirred to dissolve, and then a sodium hydroxide-water solution is added dropwise to generate a precipitate, which is filtered and washed with hot water to obtain porous chitosan beads, which are recorded as CS; S2, adding the CS obtained in step S1 to deionized water, first adding formaldehyde-water solution to react under stirring conditions, then adding glutaraldehyde to carry out cross-linking reaction, filtering, washing, and obtaining porous, cross-linked chitosan beads, which are recorded as CS-GD; S3, adding the CS-GD obtained in step S2 to an ethanol-water solution, first adding epichlorohydrin to react under stirring conditions, the obtained product is recorded as CS-ECH, then adding ethylenediamine to react, filtering, washing, and the obtained product is recorded as CS-EDA; S4, soaking the CS-EDA obtained in step S3 with hydrochloric acid, then washing with deionized water until neutral, and adding it together with 2-chloromethylpyridine hydrochloride and sodium carbonate to an ethanol-water solution, heating it to 85-95°C under stirring conditions, allowing the reactants to react in a reflux system for 24-28 hours, filtering, washing, and obtaining the modified porous chitosan beads, recorded as CS-Py.

7. The method for preparing modified porous chitosan beads capable of selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to claim 6, characterized in that: In step S4, the mass ratio of the CS-EDA to the 2-chloromethylpyridine hydrochloride and the sodium carbonate is (1-2): (1.5-3): 1, and the solid-liquid ratio of the CS-EDA to the ethanol-water solution is (0.01-0.02): 1 g / mL; in the ethanol-water solution, the volume ratio of ethanol to water is 1: (0.5-1); the concentration of the hydrochloric acid is 0.5-1 M, and the time for soaking the CS-EDA in the hydrochloric acid is 10-14 h; and the washing refers to washing with ethanol and deionized water in sequence.

8. The method for preparing modified porous chitosan beads capable of selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to claim 6, characterized in that: In step S3, the solid-liquid ratio of the CS-GD to the ethanol-water solution is (0.01-0.02):1 g / mL; the volume ratio of the epichlorohydrin, the ethylenediamine and the ethanol-water solution is (0.3-0.5):1:40; in the ethanol-water solution, the volume ratio of ethanol to water is 1:(0.5-1); the reaction temperature is 40-60°C, and the reaction time is 6-12 h; the washing refers to washing with ethanol and deionized water in sequence.

9. The method for preparing modified porous chitosan beads capable of selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to claim 6, characterized in that: In step S1, the mass ratio of the chitosan to the polyethylene glycol 2000 is 1:(0.5-2), the solid-liquid ratio of the chitosan to the acetic acid-water solution is (0.02-0.05):1 g / mL, the volume ratio of the sodium hydroxide-water solution to the acetic acid-water solution is (5-10):1; the acetic acid concentration in the acetic acid-water solution is (0.5-1)%, and the sodium hydroxide concentration in the sodium hydroxide-water solution is (0.5-1)%.

10. The method for preparing modified porous chitosan beads capable of selectively adsorbing nickel ions in a solution containing nickel and cobalt ions according to claim 6, characterized in that: In step S2, the solid-liquid ratio of the CS to deionized water is (0.01-0.02):1 g / mL, and the volume ratio of the glutaraldehyde to deionized water is (0.005-0.015):1; the concentration of the formaldehyde-water solution is 37-40%, the reaction temperature of the CS and the formaldehyde-water solution is 35-45°C, and the reaction time is 2-4 h; after the CS reacts with the formaldehyde-water solution, the temperature for cross-linking reaction with the glutaraldehyde is 40-60°C, and the reaction time is 2-6 h; the washing refers to washing with deethanol and deionized water in sequence.

Citation Information

Patent Citations

  • Preparation method of pyridine-functionalized chitosan adsorbent

    CN110368911A

  • Aminopyridine-containing carboxymethyl chitosan as well as preparation method and application thereof

    CN112442141A